PENGETAHUAN PENINGKATAN DAN PRODUKTIVITAS PERTANIAN MELALULUI SEMINAR ILMU TANAH DI DESA SEGODOREJO - Septi Ambar Indraningtia Sukma; Yessita Puspaningrum; Umar Khasan; Viki Nur Hidayatulloh; Mohammad Yasir Bisri; Siti Nur Khabibatul Khoiriyah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The community service activity through a soil science seminar in Segodorejo Village, Sumobito District, Jombang Regency was conducted to improve farmers’ understanding of sustainable soil management. The main problem faced by the community is the lack of knowledge regarding soil fertility, pH, and appropriate fertilizer use, which has led to a decline in agricultural productivity. The seminar, themed “Empowered Soil, Empowered Farmers”, was carried out using a participatory approach involving farmers, farmer groups (Gapoktan), and village officials. The materials covered basic soil science, the importance of maintaining nutrient balance, and environmentally friendly fertilization strategies, followed by field practice on soil pH measurement. The results showed an increase in farmers’ knowledge and skills in identifying soil conditions and using pH meters to support land management. In addition, farmers demonstrated high enthusiasm and began to apply the knowledge gained in their daily farming practices. This program was considered successful in strengthening farmers’ capacity and providing a tangible contribution to food security and sustainable agriculture in the village.